Pregnancy outcome following use of levodopa, pramipexole, ropinirole, and rotigotine for restless legs syndrome during pregnancy: a case series. Issue 9 (22nd October 2012) - Dostal, M.; Weber‐Schoendorfer, C.; Sobesky, J.; Schaefer, C.
Abstract : Background: Restless legs syndrome (RLS) is related to parity, and its symptoms may worsen during pregnancy. Treatment with levodopa or dopamine agonists is the first‐line therapy for RLS; however, there are limited data on treatment in pregnancy. We therefore assessed the safety of levodopa, pramipexole, rotigotine, and ropinirole in pregnancy. Methods: Prospective documentation of pregnancies exposed to levodopa, pramipexole, rotigotine, and ropinirole between 1998 and 2011 was evaluated as to their outcome (teratogenicity or fetotoxicity) by the Berlin Institute for Clinical Teratology and Drug Risk Assessment in Pregnancy. Results: We were able to complete 59 pregnancy outcomes exposed to RLS pharmacotherapy. For specific treatments, the numbers of exposed pregnancies/live born children/spontaneous abortions/induced abortions/malformations were as follows: levodopa only: 38/29 (one pair of twins)/3/7/3; pramipexole only: 12/9/3/0/0; rotigotine only: 2/2/0/0/0; ropinirole only: 3/2/0/1/0; levodopa combined with pramipexole: 3/3/0/0/0; levodopa combined with ropinirole: 1/1/0/0/0. No major birth defects were found with any RLS treatment, and three infants exposed to levodopa had minor anomalies. Conclusions: In our small prospective case series, there was no increased risk above baseline for major malformations or other adverse outcomes for levodopa and pramipexole. If necessary, levodopa treatment may be considered as an alternative to cabergoline, for which safety has been well documented in pregnancy. Abstract : Click here to view the accompanying paper in this issue.